Secondary White Matter Injury and Therapeutic Targets After Subarachnoid Hemorrhage - Ru, Xufang; Gao, Ling; Zhou, Jiru; Li, Qiang; Zuo, Shilun; Chen, Yujie; Liu, Zhi; Feng, Hua (Frontiers in Neurology, 2021)
Aneurysmal subarachnoid hemorrhage (SAH) is one of the special stroke subtypes with high mortality and mobility. Although the mortality of SAH has decreased by 50% over the past two decades due to advances in neurosurgery and management of neurocritical care , more than 70% of survivors suffer from varying degrees of neurological deficits and cognitive impairments, leaving a heavy burden on individuals, families and the society. Recent studies have shown that white matter is vulnerable to SAH, and white matter injuries may be one of the causes of long-term neurological deficits caused by SAH. We are delighted to see reports about the pivotal role of white matter injury in the pathophysiological processes after SAH, which mainly related to mechanical damage caused by increased intracerebral pressure and the metabolic damage induced by blood degradation and hypoxia. In the present review, we sought to summarize the pathophysiology processes and mechanisms of white matter injury after SAH, with a view to providing new strategies for the prevention and treatment of long-term cognitive dysfunction after SAH.